Medicating Georgia: Writing Doctors in the Old South. (23rd February 2023) - Ingram, Allan
Abstract: This essay looks at two medical families in Georgia between the eighteenth and nineteenth centuries, the Kollocks from Savannah and the Fort family from Milledgeville. Lemuel Kollock (1766–1823) moved there in 1792 from Connecticut to set up a medical practice. He married and had two sons and a daughter (Phineas, 1804–1872; Mary, 1806–1885; and George, 1810–1894). Phineas became a doctor and returned south after qualifying to practise in Savannah. The correspondence covers the social and professional contexts of practice, as well as the challenges of life and work in a climate like Georgia. A striking picture emerges of the place and importance of medicine in people's lives. Tomlinson Fort (1787–1859) was a native Georgian who set up in medicine in Milledgeville in 1810. He developed a wider public profile than Kollock, both as a doctor and in banking and politics. Most significantly, he published in 1849 his Dissertation on the Practice of Medicine, written in clear jargon‐free English, which gives a detailed and practical perspective on health in the deep South. These surviving writings allow us to examine the place of medicine within the distinctive conditions of the society of the time.